What is the Meat and Livestock Industry Doing to Reduce its Impact on Climate Change?. (August 2015) - Guinot, Caroline; Huang, Hsin; Legg, Wilfrid
Summary The meat and livestock industry is frequently criticised for its greenhouse gas emissions, directly from livestock production itself and indirectly from animal feed production, part of which is linked to deforestation undertaken to produce livestock feed. One of the most influential critiques was in FAO's Livestock's Long Shadow: Environmental issues and options. FAO has since revised downwards its estimate of livestock's share of GHG emissions from 18 to 14.5% and the organisation now argues that livestock can be part of the solution to climate change. The meat and livestock industry is actively involved in multi‐stakeholder actions to design cost effective mitigation strategies tailored to the diversity and complexity of the sector and the broad range of services that livestock provides. Improving environmental performance is a high priority for the meat and livestock industry. Greenhouse gas emissions per unit of production have fallen through implementing more climate‐friendly practices and by continually exploring new initiatives meat products provide. The meat and livestock industry is a vital global industry and it has been estimated that 1 billion poor people derive part of their livelihood from livestock production.